Linear, diatomic crystal: single-electron states and large-radius excitons - Adamyan, V.M.; Smyrnov, O.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
The large-radius exciton spectrum in a linear crystal with two atoms in the unit cell was obtained using the single-electron eigenfunctions and the band structure, which were found by the zero-range potentials method. The ground-state exciton binding energies for the linear crystal in vacuum appeared to be larger than the corresponding energy gaps for any set of the crystal parameters.